The Effect of Negative Equity on Mortgage Default: Evidence From HAMP’s Principal Reduction Alternative - Scharlemann, Therese C.; Shore, Stephen H. (Review of Financial Studies, 2016)
The Home Affordable Modification Program’s (HAMP’s) Principal Reduction Alternative (PRA) is a government-sponsored program to reduce the principal balances and monthly mortgage payments of troubled borrowers. We examine the effect of principal forgiveness on borrowers’ subsequent mortgage default. The program’s rules imply a kink in the relationship between principal forgiveness and a borrower’s initial equity level. Our identification strategy exploits the quasi-experimental variation in principal forgiveness generated by this kink using a regression kink design (RKD), which compares the relationship between initial equity and default on either side of the kink. We estimate that HAMP PRA reduced the quarterly default hazard from <f>3.8\ %</f> to <f>3.1\ %</f>. Received February 4, 2015; accepted August 2, 2015 by Editor Philip Strahan.